Classificação da periculosidade de componentes de resíduos de equipamentos eletroeletrônicos (REEEs) por metais não-voláteis - Sato, Leila Miho [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Os resíduos de equipamentos eletroeletrônicos (REEEs) são um grande problema ambiental e de saúde pública em todo o mundo, pois podem conter quantidades significativas de metais pesados e produtos químicos tóxicos em sua composição. Este trabalho tem como objetivo classificar alguns dos componentes críticos desses REEEs através da análise das substâncias inorgânicas presentes no mesmo. Os componentes selecionados para o estudo foram aqueles encontrados com maior frequência entre os REEEs: cabos flat e de fonte; cartuchos de tinta; toners de impressora; placas de circuito impresso (PCIs) de tipo I, II e III; tubos de raios catódicos (CRTs); e displays de cristal líquido (LCDs). Utilizou-se como base as normas brasileiras: ABNT NBR 10.004 (resíduos sólidos - classificação); ABNT NBR 10.005 (Lixiviação de resíduos); e ABNT NBR 10.007 (amostragem de resíduos sólidos), e nas normas americanas: U. S. EPA – 3015a (microwave assisted acid digestion of aqueous samples and extracts) e U. S. EPA – 6020 (inductively coupled plasma-mass spectrometry). Com base nos resultados obtidos, constatou-se que os cabos fonte e as PCIs de tipo I e II apresentam periculosidade devido aos altos valores de concentração de chumbo (Pb). Os demais componentes, tais como: PCI tipo III; LCDs; cartuchos; toners e cabos flat, podem ser classificados como resíduos de Classe II – não perigoso.

Electronic and electrical equipment waste (WEEE) is a major environmental and public health problem worldwide as it may contain significant amounts of heavy metals and toxic chemicals in its composition. This study aims to classify some of the critical components of these WEEE through the analysis of inorganic substances present in them. The components selected for the study were those found most frequently among the WEEE: flat and source cables, ink cartridges, printer toners, type I, II and III printed circuit boards (PCBs), cathode ray tubes (CRTs) and liquid crystal displays (LCDs). Brazilian standards were used as a basis: ABNT NBR 10.004 (solid waste classification); ABNT NBR 10.005 (leaching of waste); and ABNT NBR 10.007 (sampling of solid waste), and American standards: U.S. EPA - 3015a (microwave-assisted acid digestion of aqueous samples and extracts) and U.S. EPA - 6020 (inductively coupled plasma-mass spectrometry). Based on the results obtained, it was found that source cables and type I and II PCBs present danger due to high lead (Pb) concentration values. The other components such as type III PCBs, LCDs, ink cartridges, printer toners and flat cables can be classified as Class II waste - non-hazardous.
Classification of the hazard level of non-volatile metals in waste electrical and electronic equipment (WEEE).
Keywords: periculosidade; REEE; lixiviação; classificação; hazardousness; WEEE; leaching; classification